2019
DOI: 10.1017/jfm.2019.589
|View full text |Cite
|
Sign up to set email alerts
|

Diffusiophoresis, Batchelor scale and effective Péclet numbers

Abstract: We study the joint mixing of colloids and salt released together in a stagnation point or in a globally chaotic flow. In the presence of salt inhomogeneities, the mixing time is strongly modified depending on the sign of the diffusiophoretic coefficient $D_{dp}$. Mixing is delayed when $D_{dp}>0$ (salt-attracting configuration), or faster when $D_{dp}<0$ (salt-repelling configuration). In both configurations, as for molecular diffusion alone, large scales are barely affected in the dilating direction whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The channel wall is impenetrable to the solute and the colloid. The steady hydrodynamic flow v(r) is directed along the axial direction z and may vary in the radial direction r. The colloid C(r, z, t) and solute S(r, z, t) concentration fields are symmetrically distributed about the channel centreline, and may vary in the radial and axial directions, and in time t. For C S, which is common for colloidal or bacterial suspensions containing molecular solutes, the influence of the evolution of C on S is negligible (Lapidus & Schiller 1976;Rivero-Hudec & Lauffenburger 1986;Staffeld & Quinn 1989;Ford & Cummings 1992;Marx & Aitken 2000;Abecassis et al 2008;Tindall et al 2008;Palacci et al 2010Palacci et al , 2012Kar et al 2015;Banerjee et al 2016;Shi et al 2016;Shin et al 2016;Ault et al 2017Ault et al , 2018Peraud et al 2017;Shin et al 2017;Balu & Khair 2018;Raynal et al 2018;Raynal & Volk 2019;Shim et al 2019;Chu et al 2020a). The advection-diffusion transport of the solute is governed by…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The channel wall is impenetrable to the solute and the colloid. The steady hydrodynamic flow v(r) is directed along the axial direction z and may vary in the radial direction r. The colloid C(r, z, t) and solute S(r, z, t) concentration fields are symmetrically distributed about the channel centreline, and may vary in the radial and axial directions, and in time t. For C S, which is common for colloidal or bacterial suspensions containing molecular solutes, the influence of the evolution of C on S is negligible (Lapidus & Schiller 1976;Rivero-Hudec & Lauffenburger 1986;Staffeld & Quinn 1989;Ford & Cummings 1992;Marx & Aitken 2000;Abecassis et al 2008;Tindall et al 2008;Palacci et al 2010Palacci et al , 2012Kar et al 2015;Banerjee et al 2016;Shi et al 2016;Shin et al 2016;Ault et al 2017Ault et al , 2018Peraud et al 2017;Shin et al 2017;Balu & Khair 2018;Raynal et al 2018;Raynal & Volk 2019;Shim et al 2019;Chu et al 2020a). The advection-diffusion transport of the solute is governed by…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…where u r (r, z, t) and u z (r, z, t) are the radial and axial components of the chemical flow, respectively. In diffusiophoresis, D c is the constant, intrinsic diffusivity of the colloid (Staffeld & Quinn 1989;Abecassis et al 2008;Palacci et al 2010Palacci et al , 2012Kar et al 2015;Banerjee et al 2016;Shi et al 2016;Shin et al 2016;Ault et al 2017Ault et al , 2018Shin et al 2017;Raynal et al 2018;Raynal & Volk 2019;Chu et al 2020a). In chemotaxis, D c is the random motility of the microorganism.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…For both the turbulent clustering of floaters and that of inertial particles the effective compressibility is related to some underlying coupling to the overall turbulent mixing process. In recent studies [15][16][17][18][19] our groups have shown that similar compressible effects on the transport and mixing properties of particles can be induced by the particle response (a so-called phoretic drift)-to environmental field gradients. This environment sensing strategy can be built from various phoretic phenomena: diffusiophoresis (drift induced by chemical concentration gradients), thermophoresis (drift induced by thermal gradients), electrophoresis (drift induced by electric field gradients), etc.…”
Section: Introductionmentioning
confidence: 99%
“…This environment sensing strategy can be built from various phoretic phenomena: diffusiophoresis (drift induced by chemical concentration gradients), thermophoresis (drift induced by thermal gradients), electrophoresis (drift induced by electric field gradients), etc. Experiments, simulations, and analytical models [15][16][17][18][19] show that such phoretic particles acquire an effectively compressible dynamics, even though the underlying flow is perfectly incompressible. Active (self-propelled) particles, which can be seen as an extreme case of phoretic particles (with self-generated gradients driving their drift), have also been reported to exhibit clustering when stirred by incompressible chaotic or turbulent flows [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation